Pendidikan Kecakapan Hidup (Life Skill) Untuk Anak Usia Dini - Nadya Safira; Anugrah Hidayah (Jurnal Indonesia Sosial Teknologi, 2022)
Early childhood is a golden period of child development where all aspects of development and intelligence can be easily stimulated. Early age is also a unique period of child development to go through a phase called the sensitive period, egocentric period, imitation period, group period, exploration period and rebellious period. Therefore, early childhood has not been able to control emotions, not independent, not able to distinguish between good and bad deeds, wants to win on their own, has not been able to socialize with their environment and so on. For this reason, early childhood is a very decisive period in the formation of a child's life skills so that efforts are needed to stimulate, educate, guide, nurture and provide learning activities that will produce and improve children's abilities and skills. Because this golden period only lasts once in a phase of human life. Therefore, at an early age, holistic education efforts need to be made.